(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
The Philippines relies significantly on swine-related enterprises for food security and economic stability. The sector has faced numerous restraints in recent years and remains considerably distant from reaching the production target for domestic consumption. This study aims to identify the key drivers of the nation’s pork production in recent years, thereby enhancing our understanding of what is needed to make the industry sustainable in the future. A comprehensive review was conducted using keyword-based searches across major databases and official reports (2018–2023) to assess pig production, consumption, technology adoption, and sustainability in the Philippines. The extracted data were analyzed using Pearson correlation analysis in IBM SPSS Statistics 20 to examine the relationships among key production factors. Most of the existing problems identified through this review are somehow related to small-scale operation. Large-scale commercial farms have solutions to many of these issues, and a gradual expansion of their operations is recommended. We observed a powerful negative linear relationship between domestic pork production and pork importation (r = −0.949). Pork importation contributes to retail price hike (r = 0.948) and is negatively related to consumption (r = −0.815), indicating that increasing national production is mandatory for stabilizing the market. A rapid transition to commercial systems is not feasible, as many farmers would be left with no alternatives if the government were to cease support. Consistent guidance, support, and monitoring from the government and other responsible entities can help build awareness, establish cooperative farms, and achieve sustainability. J. Adv. Vet. Anim. Res., 12(4): 1168–1191, December 2025 http://doi.org/10.5455/javar.2025.l978